Association between Absolute Tumor Burden and Serum Bone‐Specific Alkaline Phosphatase in Canine Appendicular Osteosarcoma. (4th June 2013) - Sternberg, R.A.; Pondenis, H.C.; Yang, X.; Mitchell, M.A.; O'Brien, R.T.; Garrett, L.D.; Helferich, W.G.; Hoffmann, W.E.; Fan, T.M.
<x xml:space="preserve">Abstract</x> Background In dogs with appendicular osteosarcoma (OSA), increased pretreatment serum bone‐specific alkaline phosphatase (BALP) activity is a negative prognostic factor, associated with shorter disease‐free intervals and survival times, but a biologic basis for observed differential serum BALP activities in canine OSA patients remains incompletely defined. Objective Serum BALP activity will correlate with absolute tumor burden in dogs with OSA. Animals This study included 96 client‐owned dogs with appendicular OSA. Methods In canine OSA cell lines, the expression and membranous release of BALP was evaluated in vitro. The correlation between serum BALP activity and radiographic primary tumor size was evaluated in OSA‐bearing dogs. In dogs developing visceral OSA metastases, serial changes in serum BALP activities were evaluated in relation to progression of macroscopic metastases, and visceral metastatic OSA cells were evaluated for BALP expression. Results In vitro, BALP expression was not associated with either tumorigenic or metastatic phenotype, rather the quantity of membranous BALP released was proportional with cell density. In dogs devoid of macroscopic metastases, there was a positive correlation between serum BALP activity and absolute primary tumor size. In dogs with progressive OSA metastases, serum BALP activity increased and coincided with the development of macroscopic metastases. OSA cells derived from visceral metastatic lesions retained BALP expression. Conclusions and Clinical Importance Tumor burden is a determinant of serum BALP activity in dogs with appendicular OSA. The association between increased pretreatment BALP activity and negative clinical prognosis may simply be attributed to greater initial tumor burden, and consequently more advanced tumor stage.